Penerapan Model Kooperatif Jigsaw Dalam Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Kewirausahan - Sri Hartati S (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
Jigsaw is cooperative learning or working together by dividing students into groups and interdependent responsibility independently. Each group is responsible for completing the part of the lesson material that must be learned and convey the material to the original group. Learning outcomes are a result of student learning which includes various aspects cognitive, affective and psychomotor which can be seen from the final evaluation of learning. With skills obtained by students after receiving lessons from the teacher so they can develop knowledge in everyday life. Learning by applying the Jigsaw cooperative model can improve student learning outcomes. This proved that there was an increase in student learning outcomes in each cycle. In the first cycle, the average value of student learning outcomes was 61.78%. Then in the second cycle the average value of student learning outcomes is 67.5%. There is an increase in the average value of cycle 1 to II of 5.72%.